2016
DOI: 10.12783/issn.2328-2967/57/4/1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Online Students’ Behaviors on Course Sites and the Effect on Learning Performance: A Case Study of Four LIS Online Classes

Abstract: This research investigated the relationship between online students' behaviors in a learning management system and their learning performance, as measured by their final grades. Four online information technology classes in a major U.S. library and information science program were studied. The course sites' log data, as well as the students' final grades were analyzed at both the class level and the general level using the aggregated data from all four classes. The results show that the number of days students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other researchers have also found that students regularly access the syllabus, indicating its' perceived value among students. For example, in a study by Zhang (2016), students in four different classes, two introductory and two advanced, at a research university accessed the syllabus via the learning management system between nine and 14 times per semester on average. In one of the courses, there was a significant correlation between accessing the syllabus and the final course grade, with increases in access being associated with higher final course grades (Zhang, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have also found that students regularly access the syllabus, indicating its' perceived value among students. For example, in a study by Zhang (2016), students in four different classes, two introductory and two advanced, at a research university accessed the syllabus via the learning management system between nine and 14 times per semester on average. In one of the courses, there was a significant correlation between accessing the syllabus and the final course grade, with increases in access being associated with higher final course grades (Zhang, 2016).…”
mentioning
confidence: 99%
“…For example, in a study by Zhang (2016), students in four different classes, two introductory and two advanced, at a research university accessed the syllabus via the learning management system between nine and 14 times per semester on average. In one of the courses, there was a significant correlation between accessing the syllabus and the final course grade, with increases in access being associated with higher final course grades (Zhang, 2016). In a study conducted by Calhoon and Becker (2008), students, who were mostly first and second-year students studying at a small university, also reported regularly referring to their syllabus, with almost half of the students indicating that they reviewed the syllabus on the same day as their class.…”
mentioning
confidence: 99%